Mobile money for women's economic empowerment: the mediating role of financial management practices - Gregor Dorfleitner; Quynh Anh Nguyen (Review of Managerial Science, 2022)
This article examines whether mobile money adoption contributes to women's economic empowerment, and considers the mediating effect of financial management behavior. Cross-sectional data analysis is conducted utilizing a sample of women in seven countries across South Asia and Sub-Saharan Africa. We also investigate whether these effects vary between rural and urban areas. Three measures of mobile money adoption are considered to reflect the process of engaging in mobile money services. We find supportive evidence for the impact of mobile money adoption on women's economic empowerment and the influencing mechanism of financial management behavior for the whole sample and the rural sub-sample. Moreover, the results are consistent for three alternative measures of mobile money adoption. Our findings suggest that mobile money can be harnessed to promote women's economic empowerment; however, the impact appears to be greater if women are equipped with proper financial management skills.
Keywords: 650; Mobile money; Women's economic empowerment; Financial management behavior; Mediating effect